Calcium-induced calcium release and gap junctions mediate large-scale calcium waves in olfactory ensheathing cells in situ. Issue 2 (1st August 2015) - Stavermann, Maren; Meuth, Patrick; Doengi, Michael; Thyssen, Anne; Deitmer, Joachim W.; Lohr, Christian
Graphical abstract